Analysis of U.S. Geopolitical Impact on Taiwan’s Semiconductor Market through Sharia Principles - Muhammad-Lawal, Adam Adesina; Azizi Nik Abdullah, Nik Md Saiful; Efendi, Faisal; Januaris, Fadli (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The semiconductor industry in Taiwan, led by the Taiwan Semiconductor Manufacturing Company (TSMC), plays a strategic role in maintaining global technological and economic balance. Escalating geopolitical tensions between the United States and China have reshaped the dynamics of this industry, as the U.S. implements restrictive policies on semiconductor exports to China and promotes supply chain diversification through legislation such as the CHIPS and Science Act of 2022. This study aims to analyze the geopolitical impact of U.S. policies on Taiwan’s semiconductor market through the lens of Sharia economic principles, which emphasize justice (adl), balance (mizan), and the promotion of public welfare (maslahah). Employing a qualitative descriptive approach combined with a sociological legal method, the research collects data through in-depth interviews with semiconductor industry experts, scholars of international trade law, and Islamic economic theorists. Document analysis was also conducted on policy texts, Bureau of Industry and Security (BIS) reports, export control regulations, and relevant trade statistics from WSTS and SEMI. The findings reveal that while U.S. initiatives offer short-term advantages to Taiwan by enhancing technological security and global competitiveness, they also generate long-term vulnerabilities such as dependency risks, unequal market access, and potential ethical imbalances. Viewed through Sharia principles, these dynamics highlight the importance of fairness, mutual benefit, and sustainability in global trade governance. The study concludes that applying Islamic ethical frameworks can contribute to a more just and balanced semiconductor market in the evolving geopolitical order.